BENTUK PERTUNJUKAN OPERA TIMUN EMAS KARYA JONET SRI KUNCORO - Etika Sari; nanuk rahayu (Greget, 2019)
The Opera Timun Emas is an Opera-shaped dance work in Directed by Jonet Sri Kuncoro on birthday Soeryo Soemirat Dance Workshop to 34 in 2016. Problem in this research is how the process of scrattering and how Opera Timun Emas performances. Based on the object examined this research uses qualitative methods with a process approach to and shape. To know about the process of using the the thought of Rahayu Supanggah about the garrison covering the material, facilities, and furniture, and a garage, and a Working on. Discussing form issues using form concepts Suzane K. Langer which is explained by the opinion of R. M Soedarsono Discussing elements that include dance movements, formations, makeup, fashion, Dance music, dramatic design, theme, choreography group of places Staging, lighting, and arrangement of events. The results showed that the Opera Timun Emas includes in the genre of opera dance dramas, which are directed by In consideration of the garap, penggarap, facilities, furniture, and a line of Opera Timun Emas takes the basic idea of concern for a child’s world Folklore. Portrayed by the students of the Soeryo Soemirat. The Opera Timun Emas form can be seen from the existing elements Dance, formations, makeup, fashion, dance music, dramatic design, themes, the choreography of a group of staging, lighting, and The event was directed into a intact unity.Keywords: Opera, Garap, shape.